Tuning Biosensor Cross-Reactivity Using Aptamer Mixtures - Liu, Yingzhu (Anal Chem, 2020)
It is challenging to tune the response of biosensors to a set of ligands, for example, cross-reactivity to a given target family while maintaining high specificity against interferents, due to the lack of suitable bioreceptors. We present a novel approach for controlling the cross-reactivity of biosensors by employing defined mixtures of aptamers that have differing binding properties. As a demonstration, we develop assays for the specific detection of a family of illicit designer drugs, the synthetic cathinones, with customized responses to each target ligand and interferent. We first use a colorimetric dye-displacement assay to show that the binding spectra of dual-aptamer mixtures can be tuned by altering the molar ratio of these bioreceptors. Optimized assays achieve broad detection of synthetic cathinones with minimal response toward interferents and generally demonstrate better sensing performance than assays utilizing either aptamer alone. The generality of this strategy is demonstrated with a dual-aptamer electrochemical sensor. Our approach enables customization of biosensor responsiveness to an extent that has yet to be achieved through any previously reported aptamer engineering techniques such as sequence mutation or truncation. Since multiple aptamers for the designated target family can routinely be identified via high-throughput sequencing, we believe our strategy offers a generally applicable method for generating near-ideal aptamer biosensors for various analytical applications, including medical diagnostics, environmental monitoring, and drug detection.